PREVENTION OF NON-COMMUNICABLE DISEASES IN PRESCHOOL-AGED CHILDREN THROUGH WHATSAPP GROUP MEDIA - Jeki Refialdinata; Nurhaida Nurhaida; Miftahurrahmi Fitri (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2026)
Introduction Eating habits in preschool-aged children play an important role in forming the foundation of long-term health. Low consumption of fruits and vegetables and high intake of sugary drinks have been reported to contribute to an increased risk of non-communicable diseases (NCDs) in adulthood. Nutrition education for parents is one of the main strategies for improving children’s dietary patterns. Purpose: This study aims to analyze the influence of education delivered through WhatsApp groups on changes in fruit and vegetable consumption as well as the limitation of sugary drinks in preschool-aged children at TK ’Aisyiyah Padang. Method: The study used a quasi-experimental one-group pretest–posttest design with 53 respondents (total sampling). Educational material was delivered through a WhatsApp group for one month. Result: The Wilcoxon Signed-Rank test showed an increase in knowledge scores from 30.11 to 33.30 (p 0.0001). Discussion: These findings indicate that digital-based education has the potential to become an effective, affordable, and accessible medium in family health promotion. Further research is recommended to assess actual behavior changes and include a control group